PENGARUH WAKTU PENGUKUSAN DAN FERMENTASI TERHADAP KARAKTERISTIK TAPE UBI JALAR UNGU (Ipomoea batatas var. Ayamurasaki) - Aditya, Secretly Galih; Yusa, Ni Made; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA, 2012)
The aim of this research is to know the time influence of steam and fermentation on the characteristic of purple sweet potato tape. This research used Randomized Group Design (RGD) with 2 factors. The first factor was the steam duration (20, 30 and 40 minutes) and the second was the fermentation duration (48, 60 and 72 hours). The result of this research showed that the duration of steam and fermentation gave highly significant effect on texture, color, taste, texture (score test), overall acceptance and non-significant effect on reducing sugar value, etanol value, starch value, pH level, aroma and texture (hedonic test). Thirty minutes of steam duration and 48 hours fermentation could produce purple sweet potato tape with the best characteristics and could be accepted by the panelist with texture 1.97 N, reducing sugar value 3.20%, starch value 4.30%, pH level 4.74, ethanol value 0.75%, the color was rather like, taste was like, the texture was rather soft and rather like, neutral flavor and overall acceptance was rather liked
Keywords: steaming, fermentation, purple sweet potato tape